Not All Patients Undergoing Stabilization of Impending Pathologic Fractures for Renal Cell Carcinoma Metastases to the Femur Need Preoperative Embolization. Issue 3 (March 2018) - Jernigan, Edward W.; Tennant, Joshua N.; Esther, Robert J.
Abstract: Background: Preoperative transarterial embolization has been utilized in the surgical treatment of metastatic renal cell carcinoma of the femur to decrease perioperative blood loss. However, few studies have documented its efficacy in decreasing the proportion of patients receiving transfusions in the setting of prophylactic treatment of impending pathologic femur fractures. Questions/purposes: In a population of patients with metastatic renal cell carcinoma of the femur who underwent prophylactic fixation, the purpose of this study was to quantify and compare the proportion of patients who received at least one transfused unit of blood between a group treated with preoperative embolization and a group without preoperative embolization. Methods: A retrospective study was performed using a Medicare claims-based database. International Classification of Diseases, 9 th Revision and Current Procedural Terminology codes were used to identify 1285 patients with metastatic renal cell carcinoma of the femur who underwent prophylactic fixation. The proportion of patients who received one or more blood transfusions was compared between 135 patients who underwent preoperative embolization and a group of 1150 concurrent control patients who did not undergo preoperative embolization. The control group was older than the embolization group, with 44% of these patients > 75 years old and 33% of the embolization group > 75 years. There was no difference in the female:male ratio between groups. Statistical comparisons of outcomes related to transfusion percentages were performed using Pearson chi square analysis with p < 0.05 considered significant. With the numbers available, we had 80% power to detect a difference in the percentage of patients transfused of 11% between the study groups at α = 0.05. Results: No difference in transfusion percentage was observed between preoperative transarterial embolization (41 of 135 [30%]) and the control group (359 of 1150 [31%]; relative risk, 0.973; 95% confidence interval, 0.743-1.274; p = 0.84). The percentage of all patients who received a transfusion was 31% (400 of 1285). Conclusions: Preoperative embolization may not be mandatory in the prophylactic treatment of metastatic renal cell carcinoma of the femur, as demonstrated by the 69% of patients who received zero units of blood despite not receiving embolization. However, assessment of the efficacy of embolization in decreasing blood loss in the current study is limited as a result of biases associated with the database design of the study; the decision of whether to send a patient for embolization should be made on a case-by-case basis. The current study does not identify specific risk factors that should factor into this decision and underscores the need for further research in this regard. A plausible future research design to account for the low numbers and selection bias that limited the current study as well as the existing studies might be a multicenter, retrospective case-control study. Level of Evidence: Level III, therapeutic study.